ENHANCING SAFETY AND SECURITY IN INDONESIAN WATERS: COOPERATIONS WITHIN DIPLOMACY FRAMEWORK - Buntoro, Kresno (Jurnal Pertahanan & Bela Negara, 2014)
The Indonesian waters is for world seaborne trade, military and naval movement, and other maritime interests. So it has a strategic value for maintaining economic security, peace, and stability in the region. Indonesia has the responsibility to address the challenges presented by activities conducted in its waters, such as marine pollution, depletion of marine resources and criminal activities at sea. These challenges also arise out of the fact that there are only a few provisions in the United Nations Law of the Sea Convention which regulate the obligations of ships or user states to share the burden faced by states which possess sea lanes of communication. The purpose of this paper is to provide an overview of maritime security challenges within Indonesia in light of its obligations to ensure safety of navigation and security. A number of recommendations are brought up to show efforts have been made by Indonesia in maintaining the safety and security in its waters in the light of defense and naval diplomacy.Â Keywords: maritime safety and security, Indonesian waters, cooperation, diplomacy